Analysis of Cooperative Performance Efficiency Levels at the Puskopdit Timor Primary Credit Cooperative in Kupang City - Djuang, Maria; Man, Stanis; Seran, Paskalis; Manafe, Henny Angri; Niha, Simon Sia (Dinasti Publisher, 2026)
This study aims to analyze the performance efficiency level of cooperatives in 13 Primary Credit Cooperatives of Puskopdit Timor in Kupang City from 2021 to 2023 using the Data Envelopment Analysis (DEA) method and variable return to scale assumptions. Efficiency is achieved when the amount of input produces a greater amount of output. Inputs include the number of members, capital, assets, and expenses, while outputs are income and surplus. The analysis results show that eight credit unions were efficient during 2021-2023. Kopdit Solidaritas achieved efficiency in 2022 and 2023. Kopdit Sami Jaya, Timau Indah, and Harapan Sejahtera were only efficient in 2023. Kopdit Familia was the credit union that did not achieve efficiency during 2021-2023. Factors causing differences in efficiency levels between credit unions include: Low member participation experienced by the five credit unions that were not yet efficient; Idle capital (Kopdit Sami Jaya, Solidaritas, Familia, and Timau Indah); Non-productive assets (Kopdit Solidaritas, Familia (2021, 2022), Timau Indah (2022), and Harapan Sejahtera. High operational costs, only Kopdit Sami Jaya. The strategy for inefficient credit unions is to improve their input management by following the benchmark credit unions. Kopdit Sami Jaya, Familia, and Timau Indah refer to Kopdit Adiguna and Harmoni Jaya. Kopdit Solidaritas refers to Kopdit Adiguna. Kopdit Familia refers to Kopdit Embu Welu (2021). Kopdit Harapan Sejahtera refers to Kopdit Sesawi Mandiri and USP Kopsen Kasema.